ALTERNATIF PENYELESAIAN SENGKETA UNTUK MENJAMIN KEADILAN PELAYANAN RUMAH SAKIT PASIEN PESERTA BPJS KESEHATAN: ALTERNATIVE DISPUTE RESOLUTION TO ENSURE FAIRNESS IN HOSPITAL SERVICES FOR BPJS HEALTH PARTICIPANTS - Sigiro, Grace Tasya (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
Health is a fundamental right constitutionally guaranteed under the 1945 Constitution of the Republic of Indonesia. In fulfilling this obligation, the government established the National Social Security System through Law No. 40 of 2004 and the Social Security Administration Agency (BPJS) through Law No. 24 of 2011. BPJS Health is mandated to administer the National Health Insurance Program (JKN) to ensure equitable and comprehensive health protection for all citizens. However, in practice, BPJS Health participants continue to encounter various challenges in hospital-based health services, including discriminatory treatment, unequal access, disparities in service quality, and constraints related to financing and administrative procedures. This study aims to examine the extent to which the principle of fairness is fulfilled within the regulatory framework governing hospital health services for BPJS Health participants. Employing a normative legal research method, the study utilizes legislative, conceptual, and analytical approaches and is analyzed descriptively and qualitatively. The findings indicate that efforts to uphold the principle of fairness have been incorporated into regulations addressing service accessibility, quality standards, transparency, and monitoring and evaluation mechanisms. Nevertheless, the principle of fairness has not been fully realized, particularly with regard to distributive and procedural justice, as evidenced by persistent disparities in service delivery. These findings suggest the need for strengthened regulatory enforcement and systemic reforms to ensure equitable health services for all BPJS Health participants.